2020
DOI: 10.3390/s20061774
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Intelligent Fault Diagnosis Method for Rolling Bearing Based on Integrated Weight Strategy Features Learning

Abstract: Intelligent methods have long been researched in fault diagnosis. Traditionally, feature extraction and fault classification are separated, and this process is not completely intelligent. In addition, most traditional intelligent methods use an individual model, which cannot extract the discriminate features when the machines work in a complex condition. To overcome the shortcomings of traditional intelligent fault diagnosis methods, in this paper, an intelligent bearing fault diagnosis method based on ensembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Shi et al proposed an intelligent fault diagnosis method based on deep learning and particle swarm optimization support vectors machine [10]. He et al reported an intelligent bearing fault diagnosis method based on sparse autoencoder [11]. In [12], authors proposed a CNN model based on dislocation time series for fault diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al proposed an intelligent fault diagnosis method based on deep learning and particle swarm optimization support vectors machine [10]. He et al reported an intelligent bearing fault diagnosis method based on sparse autoencoder [11]. In [12], authors proposed a CNN model based on dislocation time series for fault diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although model-based methods do work and achieve an extraction of an accurate HI, they still have two deficiencies: (1) Feature selection is heavily dependent on prior knowledge and diagnostic expertise. Moreover, it often focuses on a specific fault type, and thus it may be unsuitable for other faults [27,28]. (2) In real industries, acquired signals are usually exposed to environmental noises, and are transient and non-stationary.…”
Section: Introductionmentioning
confidence: 99%
“…(2) In real industries, acquired signals are usually exposed to environmental noises, and are transient and non-stationary. Therefore, signal processing technologies need to be employed to filter the collected signals, which can result in a loss of information [27,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, [ 3 ] incorporates a shallow artificial neural network to scan-chains (using failure feature vectors). The mentioned papers utilize shallow networks, whereas in [ 4 ], the authors implement a deep network in form of a stacked autoencoder for the fault diagnosis of roll bearings. Similarly, in [ 5 ], the authors present convolutional a deep neural network to classify the potential faults.…”
mentioning
confidence: 99%